Utilizing restricted mean duration of response for efficacy evaluation of cancer treatments. (21st February 2022) - Huang, Bo; Tian, Lu
Abstract: In oncology clinical trials, response‐based endpoints (time to response, objective response, duration of response [DOR]) are commonly used to detect therapeutic effect to support proof‐of‐concept or submission decisions. The restricted mean DOR (RMDOR) was recently proposed as a composite nonparametric method to efficiently quantify the treatment effect related to tumor reductions, which offers an intuitive way to perform statistical inference in cross‐arm comparison and has since been applied in some Phase III studies. In this paper, we provide further technical details and asymptotic properties of the RMDOR method and discuss the selection of the truncation time. A simulation study is conducted comparing the performance of the proposed method with existing standard methods in hypothesis testing and quantification of treatment efficacy. We use two oncology Phase III examples to illustrate the method. An R package PBIR and a SAS macro are available to perform statistical inference based on the RMDOR.